Diagnosis of the empathic situation in students of physioteraphy: cross-sectional study (2018)
Objective: Diagnosis of the empathic situation in the physiotherapy students of the Simón Bolívar University. Barranquilla. Colombia. Material and methods: Transversal study. Empathy levels were measured in 430 students along with the reliability of the data. The mean and deviation were estimated in two factors: Gender and Courses. The data were processed using a bifactorial variance analysis (model III), calculated the effect size, the power of the test and the Possible Growth Potential of the empathy and of each of its components considering the gender. The level of significance was α≤0.05 and β≥0.80. The SPSS 22.0 program was used. Results: There are differences between courses but not between gender. The differences between courses were observed in empathy in general and two of its components and all possible growth potential were positive. Conclusions: The empathic decline model is not met, there are no differences between the genders and the factors studied explain the empathic behavior observed. The characteristics indicated constitute the diagnosis of the empathic situation and constitute a guide to construct an intervention.